Guidelines for developing an at-sea fishery observer programme - Davies, S.I.; Reynolds, J.E. (Roma (Italia), 2003)
Sumario (En)
Ilus., 38 ref.
Keywords: RECURSOS MARINOS; TAXONOMIA; ANATOMIA ANIMAL; PLANTAS ACUATICAS; REGLAMENTACIONES